2014
DOI: 10.1001/jama.2014.14601
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Findings Among Patients Referred for Clinical Whole-Exome Sequencing

Abstract: IMPORTANCE Clinical whole-exome sequencing is increasingly used for diagnostic evaluation of patients with suspected genetic disorders. OBJECTIVE To perform clinical whole-exome sequencing and report (1) the rate of molecular diagnosis among phenotypic groups, (2) the spectrum of genetic alterations contributing to disease, and (3) the prevalence of medically actionable incidental findings such as FBN1 mutations causing Marfan syndrome. DESIGN, SETTING, AND PATIENTS Observational study of 2000 consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

46
766
9
17

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 1,229 publications
(838 citation statements)
references
References 34 publications
46
766
9
17
Order By: Relevance
“…The first of these was reported by the Baylor College of Medical Genetics Laboratory which demonstrated a 25% molecular diagnostic rate for 250 probands with varying indications (although 80% had a neurologic phenotype) 16. Interestingly, when they increased the number of patients to 2000, the diagnostic rate remained 25% 17. The Lee et al study of 814 patients who underwent WES in a clinical diagnostic laboratory reported a similar diagnostic rate of 22–31% 18.…”
Section: Impact Of Next‐generation Sequencing On Rare Disease Diagnosismentioning
confidence: 97%
See 4 more Smart Citations
“…The first of these was reported by the Baylor College of Medical Genetics Laboratory which demonstrated a 25% molecular diagnostic rate for 250 probands with varying indications (although 80% had a neurologic phenotype) 16. Interestingly, when they increased the number of patients to 2000, the diagnostic rate remained 25% 17. The Lee et al study of 814 patients who underwent WES in a clinical diagnostic laboratory reported a similar diagnostic rate of 22–31% 18.…”
Section: Impact Of Next‐generation Sequencing On Rare Disease Diagnosismentioning
confidence: 97%
“…Over the past 2–3 years, several large studies have demonstrated the diagnostic utility of WES for a large number of patients analyzed in clinical diagnostic laboratories 16, 17, 18. The first of these was reported by the Baylor College of Medical Genetics Laboratory which demonstrated a 25% molecular diagnostic rate for 250 probands with varying indications (although 80% had a neurologic phenotype) 16.…”
Section: Impact Of Next‐generation Sequencing On Rare Disease Diagnosismentioning
confidence: 99%
See 3 more Smart Citations